2010
DOI: 10.1002/micr.20791
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of SIEA flaps using the retrograde internal mammary system

Abstract: Superficial inferior epigastric artery (SIEA) flaps are ideal for breast reconstruction when the anatomy permits it. Due to the peripheral and superficial location of the pedicle, these flaps can be complicated by vessel kinking against the remaining ribs after insetting. Here, we describe a novel method for SIEA flap salvage after kinking or avulsion of the traditional anastomosis to the internal mammary vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The secondary flap artery was anastomosed to the retrograde IMA limb in 64% (16/25) of cases. This reflects the practical ease of a single recipient site and the well-documented adequate retrograde arterial flow ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 81%
“…The secondary flap artery was anastomosed to the retrograde IMA limb in 64% (16/25) of cases. This reflects the practical ease of a single recipient site and the well-documented adequate retrograde arterial flow ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 81%
“…Another important point to consider in this analysis is the fact that flow dynamics in the flap and surrounding tissues changes over time. 12 Flow often increases in the immediate postoperative period when the patient's core temperature and blood pressure return to normal and vasospasm dissipates. Veins also dilate to varying degrees in response to the increased pressure and flow.…”
Section: Discussionmentioning
confidence: 98%
“…6,7 Very recently, several case series have shown that the retrograde limb of the internal mammary vein can be successfully utilized as an additional outflow tract in free flap transfer. [8][9][10][11][12] Although the presence of retrograde blood flow through the distal vein following microvascular anastomosis has been documented, it has neither been quantified nor compared with the antegrade vein. Quantitative analysis of flow through the retrograde internal mammary vein (RIMV) would help to determine its reliability as a recipient blood vessel when a secondary source of venous outflow is required to prevent flap venous congestion, or as a primary source of venous outflow when the antegrade internal mammary vein (AIMV) is not an option.…”
mentioning
confidence: 99%
“…5,7,26 Based on this evidence, the use of RIMV is empowered in clinical practice. [1][2][3]10 However, the use of RIMV during DIEP flap breast reconstruction was not solely used for primary flap drainage but was mostly used for super drainage purposes as a second vein. It is unknown whether RIMV as the sole venous drainage was sufficient.…”
Section: Discussionmentioning
confidence: 99%